Pengujian Penanaman Padi Hibrida di Purwakarta - HASTINI, TRI; PERMADI, KARSIDI (Agrotrop : Journal on Agriculture Science, 2015)
Hybrid Rice Planting Assessment in Purwakarta Hybrid rice planting assessment was conducted at lowland area in Wanasari village, Wanayasa subdistrict, Purwakarta district during second dry season 2008. Seven varieties of hybrid rice namely Mapan 02, Pioner PP II, SL 8 SHS, Pioner PP I, HIPA 3, HIPA 4 and HIPA 6 were evaluated to find out hybrid rice varieties that are suitable to the agroecosystem. The observations were done for number of tillers, number of panicle per hill, number of productive panicle per hill, panicle length, number of filled-grain per panicle, number of unfilled-grain per panicle, plant height, and yield. Descriptive statistics analysis showed that the most number of panicle was 17.67 on SL 8 SHS and the least was 8.67 on HIPA 3, while the highest number of productive panicle was 15.67 on Pioner PP I and the least was 6.3 on HIPA 3. The longest of panicle was 6.90 cm on Pioner PP I and the shortest was 6.36 cm on HIPA 3. The highest number of well-filled grain was 75.18 on Pioner PP I, but it has 195.80 unfilledgrain. The lowest number of well-filled grain was 52.88 on HIPA 3 and the lowest unfilled-grain was 108.40 on Mapan 02. The highest plant was HIPA 6 with the height of plant was 93 cm, and the lowest was Mapan 02 with the height of plant was 78.06 cm. While the most number of tillers was 21.8 on HIPA 6, and the lowest was 15.88 on Pioner PP II. The highest yield was 5.84 t ha-1 on Pioner PP I and the lowest was 3.76 t ha-1 on SL 8 SHS. According to agronomic characters and the yield, the most appropriate rice hybrid to plant at Wanasari village, Wanayasa sub-district, Purwakarta district during second dry season was Pioner PP I.
Keywords: hybrid rice; lowland; second dry season.